2016
DOI: 10.1371/journal.pone.0166596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Control Strategies for Porcine Reproductive and Respiratory Syndrome (PRRS) in Swine Breeding Herds Using a Discrete Event Agent-Based Model

Abstract: The objective of this study was to develop a discrete event agent-based stochastic model to explore the likelihood of the occurrence of porcine reproductive and respiratory syndrome (PRRS) outbreaks in swine herds with different PRRS control measures in place. The control measures evaluated included vaccination with a modified-live attenuated vaccine and live-virus inoculation of gilts, and both were compared to a baseline scenario where no control measures were in place. A typical North American 1,000-sow far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Other model limitations include that specific herd or farm structure, known to influence within-herd transmission dynamics of pathogens (see e.g. [48,49,51]), were not explicitly considered in our model. Furthermore, we only considered horizontal infection transmission in this study, thus ignoring the potential impact of vaccination on vertical transmission from infected sows or boars to piglets from the time of insemination during gestation until after birth [25,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other model limitations include that specific herd or farm structure, known to influence within-herd transmission dynamics of pathogens (see e.g. [48,49,51]), were not explicitly considered in our model. Furthermore, we only considered horizontal infection transmission in this study, thus ignoring the potential impact of vaccination on vertical transmission from infected sows or boars to piglets from the time of insemination during gestation until after birth [25,64].…”
Section: Discussionmentioning
confidence: 99%
“…The model presented in equations (1)-(2) above can be applied to model PRRSv transmission dynamics in pig herds under different vaccination scenarios [48,49,51]. Values of the model parameters were obtained from the literature (see references listed in Table 2) and represent different PRRSv strains (e.g.…”
Section: Application To Prrsmentioning
confidence: 99%
“…In addition to direct contact among farms via animal movements, indirect contact may occur between farms due to windborne propagation of aerosols and dissemination of fomites by personnel, contaminated vehicles, and feed (Alonso et al, 2014;Alvarez et al, 2016;Beam et al, 2015;Dee et al, 2014;Kim et al, 2017;Lowe et al, 2014;O'Dea et al, 2015;Pasick et al, 2014). Although the potential importance of such mechanisms in creating transmission opportunities between swine premises has been shown in experimental studies and outbreak investigations (Alonso et al, 2014;Bowman et al, 2015;Lowe et al, 2014;Pasick et al, 2014), indirect contact is less often accounted for in epidemiological models (Arruda et al, 2016;Martinez-Lopez et al, 2011;Thakur et al, 2015;Yadav et al, 2016). Models of pathogen spread in livestock populations focus primarily on animal movement and, in some cases, local spatial spread based on proximity between premises (Brooks-Pollock et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling has been used as an important tool to help understand the dynamics of infectious diseases among farm animals. However, mathematical models for describing the spread of PRRSV are not numerous [9][10][11][12][13]. Evans et al [9] developed a stochastic model of a farrow-finish heard and found that the persistence of PRRSV increases according to increased herd size, increased contact between different age groups, and increased reintroduction of infectious swines.…”
Section: Introductionmentioning
confidence: 99%